Physical Education in integrated High School: Analysis of theses and dissertations defended in Brazilian post-graduation programs (Research, Society and Development, 2021)
This research focused on mapping and analyzing the academic production in theses and dissertations – defended in Brazilian post-graduation programs – related to Physical Education in integrated high school (IHS) topics. This investigation is characterized as a research of quali-quantitative approach with bibliographic design and bibliometric analysis. The search for the academic productions was made in two Brazilian databases through the descriptors “Physical Education” and “integrated high school” utilizing the boolean operator AND. It was concluded that Physical Education manifests itself in a singular way in each institution where IHS is offered and the subject is an essential curricular component for this course modality due to its ability to contribute to integral formation of students.